Psychological and Cultural Factors Influencing Career Indecision in First-Generation Students - Ríos, Juan Camilo; Fernández, Lucía (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aims to explore the psychological and cultural factors that contribute to career indecision among first-generation university students.Methods and Materials: A qualitative research design was employed using semi-structured, in-depth interviews with 25 first-generation undergraduate students enrolled in public universities across Argentina. Participants were selected through purposive sampling to ensure diversity in gender, field of study, and academic standing. Data collection continued until theoretical saturation was achieved. Interviews were transcribed verbatim and analyzed thematically using NVivo software, following open, axial, and selective coding procedures. The analysis yielded four main thematic categories: internal psychological conflict, family and socio-cultural expectations, structural and informational barriers, and social comparison and belonging uncertainty.Findings: Thematic analysis revealed that internal psychological factors such as low self-efficacy, perfectionism, emotional overwhelm, and fear of failure significantly hindered participants’ ability to make confident career decisions. Cultural and familial expectations created added pressure to choose traditionally prestigious and economically secure careers, often in conflict with personal interests. Structural barriers, including inadequate career guidance and informational inequities, further complicated decision-making processes. Lastly, many students experienced intense social comparison and imposter syndrome, contributing to a sense of alienation and emotional vulnerability. These themes interact dynamically, creating a complex and layered portrait of career indecision rooted in both individual and systemic dimensions.Conclusion: Interventions must move beyond standardized career guidance to incorporate culturally sensitive, psychologically supportive, and structurally informed approaches tailored to the unique challenges faced by this population.